The plasma proteome is favorably modified by a high protein diet but not by additional resistance training in older adults: A 17-week randomized controlled trial - Franzke, Bernhard; Bileck, Andrea; Unterberger, Sandra; Aschauer, Rudolf; Zöhrer, Patrick A.; Draxler, Agnes; Strasser, Eva-Maria; Wessner, Barbara; Gerner, Christopher; Wagner, Karl-Heinz (Frontiers in Nutrition, 2022)
Background: The age-related loss of muscle mass significantly contributes to the development of chronic diseases, loss of mobility and dependency on others, yet could be improved by an optimized lifestyle. Objective: The goal of this randomized controlled trial was to compare the influence of a habitual diet (CON) with either a diet containing the recommended protein intake (RP) or a high protein intake (HP), both with and without strength training, on the plasma proteome in older adults. Methods: 136 women and men (65-85 years) were randomly assigned to three intervention groups. CON continued their habitual diet; participants of the HP and RP group consumed either high protein or standard foods. After 6 weeks of dietary intervention, HP and RP groups additionally started a strength training intervention twice per week for 8 weeks. 24h dietary recalls were performed every 7 to 10 days. Body composition was assessed and blood taken. Plasma proteomics were assessed with LC-MS. Results: Participants of the HP group doubled their baseline protein intake from 0.80±0.31 g/kg BW/d to 1.63±0.36 g/kg BW/d; RP increased the protein intake from 0.89±0.28 g/kg BW/d to 1.06±0.26 g/kg BW/d. The CON group kept the protein intake stable throughout the study. Combined exercise and HP initiated notable changes, resulting in a reduction in bodyfat and increased muscle mass. Proteomics analyses revealed 14 significantly affected proteins by HP diet, regulating innate immune system, lipid transport and blood coagulation, yet the additional strength training did not elicit further changes. Conclusions: Combined HP and resistance exercise in healthy older adults seem to induce favorable changes in the body composition. Changes in the plasma proteome due to the high protein diet point to a beneficial impact for the innate immune system, lipid transport and blood coagulation system, all of which are involved in chronic disease development. The study was registered at clinicaltrials.gov (NCT04023513).